Comparison of Kinetics, Kinematics, and Electromyography During Single-Leg Assisted and Unassisted Cycling. Issue 6 (June 2015) - Bini, Rodrigo R.; Jacques, Tiago C.; Lanferdini, Fábio J.; Vaz, Marco A.
Abstract : Abstract: Bini, RR, Jacques, TC, Lanferdini, FJ, and Vaz, MA. Comparison of kinetics, kinematics, and electromyography during single-leg assisted and unassisted cycling. J Strength Cond Res 29(6): 1534–1541, 2015—To use single-leg cycling training for varying populations, it is important to understand whether a counterweight attached to the contralateral crank during single-leg cycling drills replicates the effects of the opposite leg in the ipsilateral leg. Therefore, we compared single-leg assisted cycling using a counterweight on the contralateral crank for joint kinetics, kinematics, and lower-limb muscle activation. Fourteen healthy nonathletes performed 2 bilateral cycling trials (240 ± 23 W and 90 ± 2 rpm) and 2 single-leg trials (120 ± 11 W and 90 ± 2 rpm) for measurements of pedal force, joint kinematics, and muscle activation of their right lower limb. For 1 single-leg trial, a custom-made adaptor was used to attach 10 kg of weight to the contralateral leg. Total force applied on the pedal, pedal force effectiveness, the mean joint angles and range of motion, mechanical work at the crank, hip, knee, and ankle joints, electromyography, pedaling cadence, and right crank mechanical work were assessed. Biceps femoris (87%), vastus lateralis (15%), rectus femoris (57%), tibialis anterior (57%), and gastrocnemius medialis (12%) activations were larger in the single-leg assisted trial compared with the bilateral trial. Lower total pedal force (17%) and increased index of effectiveness (16%) also indicate mechanical differences in single-leg cycling using a counterweight on the contralateral crank than conventional bilateral cycling. Single-leg assisted training should be used with caution because of potential differences in muscle recruitment and pedaling kinetics compared with bilateral cycling.